Proceedings of the Second Electrophysiology Symposium of the PR Chapter of the ACC - Hernández, Helder; del Rio, Valentín; Franqui, Hilton; Rodríguez-Vilá, Orlando; Sotomonte, Juan C. (Puerto Rico Health Sciences Journal, 2014)
On February 15-16, 2013 the Puerto Rico Chapter of the American College of Cardiology (ACC), co-sponsored by the Heart Rhythm Society (HRS), celebrated the 2nd Electrophysiology Symposium in San Juan, Puerto Rico. The purpose of the meeting was to review the electrocardiographic characteristics of common clinical disorders such as ventricular tachycardia (VT) and atrial tachyarrhythmias (AT/AF), as well as their clinical management. A comprehensive review of contemporary issues in cardiac device management was also presented. The faculty was constituted by five world-renowned electrophysiologists including: Samuel Asirvatham, MD; David Callans, MD; Laurence Epstein, MD; Francis Marchlinsky, MD; and Brian Olshansky, MD. The audience was constituted by general cardiologists, interventional cardiologists, cardiac electrophysiologists, and cardiovascular surgeons. The following article showcases only key topics of each lecture and is intended to focus in areas of controversy or great clinical interest.